Historical and sociological reflections for a democratic school management in Brazil - Santos, Wilson da Silva (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
This paper analyzes school management as a process that reveals to be a social phenomenon integrated in the superstructure of the State, in its dimension of civil society (the spatial organization and the cultural character of the school, etc.). The actions that take place in this dimension cause school management and organization to be conceived in their contradictions, complexities and heterogeneity. This article takes place in a sociological and historical perspective and has as theoretical-methodological framework the conceptual formulations, above all, by Florestan Fernandes, Antonio Gramsci and Vitor Henrique Paro. This theoretical-methodological framework assists us in a more refined understanding of collegiate and autonomous management as a dialectical process, which may or may not be directed to the interests of the subordinate classes. Thus, this investigation addresses the theme of school management as an educational phenomenon that has its peculiarities due to its historical moment of continuity and discontinuity.